Answer:
(x+2)(x-3)
Step-by-step explanation:
easy
Step-by-step explanation:
F( <em>x</em><em> </em><em>)</em><em> </em><em>=</em><em> </em><em>5</em><em> </em><em>(</em><em>3</em><em>)</em><em> </em><em>^</em><em> </em><em>x</em>
<em>Y</em><em> </em><em>intercept</em><em> </em>
<em>Let</em><em> </em><em>x</em><em> </em><em>=</em><em> </em><em>0</em>
<em>f</em><em>(</em><em>0</em><em>)</em><em> </em><em>=</em><em> </em><em>5</em><em>×</em><em> </em><em>3</em><em> </em><em>^</em><em> </em><em>0</em>
<em>f</em><em>(</em><em>0</em><em> </em><em>=</em><em> </em><em>5</em><em> </em><em>×</em><em> </em><em>1</em>
<em>f</em><em>(</em><em>0</em><em>)</em><em> </em><em>=</em><em> </em><em>5</em>
<em>X</em><em> </em><em>intercept</em><em> </em>
<em>let</em><em> </em><em>y</em><em> </em><em>=</em><em> </em><em>o</em>
<em>0</em><em> </em><em>=</em><em> </em><em>5</em><em> </em><em>×</em><em> </em><em>3</em><em> </em><em>^</em><em>x</em>
<em>No</em><em> </em><em>x</em><em> </em><em>intercept</em><em>/</em><em> </em><em>zero</em>
<em>therefore</em><em> </em>
<em>Vertical</em><em> </em><em>intercept</em><em> </em><em>(</em><em>0</em><em>;</em><em> </em><em>5</em><em>)</em>
<em>Domain</em><em> </em><em>XER</em>
<em>▪︎</em><em>this</em><em> </em><em>refer</em><em> </em><em>to</em><em> </em><em>the</em><em> </em><em>values</em><em> </em><em>of</em><em> </em><em>X</em>
Answer:
Step-by-step explanation:
-7y = -10x - 8
y = 10/7x + 8/7
-5, 5 there u go cuhhhhhhhhh
Answer:
√{395×395}=√395²=395 is your answer